Osteoarthritis susceptibility genes influence the association between hip morphology and osteoarthritis - Waarsing, J. H.; Kloppenburg, M.; Slagboom, P. E.; Kroon, H. M.; Houwing‐Duistermaat, J. J.; Weinans, H.; Meulenbelt, I. (Arthritis & rheumatology (Hoboken, N.J.), 2011)
Objective The identified osteoarthritis (OA) susceptibility genes are mainly active in skeletal development and could thus affect joint geometry. Because nonoptimal joint geometry is a risk factor for the development of OA, we investigated if and how the path that leads from nonoptimal joint geometry to OA of the hip is influenced by these genes. Methods The shape of the hips of subjects in the Genetics, Osteoarthritis and Progression Study, consisting of sibling pairs with symptomatic OA at multiple joint locations, was quantified by applying a statistical shape model to radiographs. Shape aspects (modes) were correlated to OA characteristics. We then tested for the association of shape modes with OA susceptibility single‐nucleotide polymorphisms (SNPs) of GDF5, FRZB, and DIO2. Results Four of 23 shape modes (mode 1, mode 17, mode 18, and mode 21) were strongly associated with OA characteristics. We observed a significant interaction between carrier status of DIO2 rs12885300 and hip OA characteristics for mode 1 (P = 0.005). This indicates that this specific aspect of hip shape correlates with OA characteristics only in carriers of the susceptibility allele. Conclusion Our results suggest that it is more likely that the rs12885300 SNP of DIO2 increases the vulnerability of cartilage to nonoptimal bone shapes rather than directly influencing the formation of these shapes.